Garden Learning: A Study on European Botanic Gardens' Collaborative Learning Processes - Kapelari, Suzanne (Ubiquity Press, 2015)
"From 2007-2013 the European 7th Framework Program Science in Society (FP7) funded a multitude of formal and informal educational institutions to join forces and engage in alternative ways to teach science-inside and outside the classroom-all over Europe. This book reports on one of these projects named INQUIRE which was developed and implemented to support 14 Botanic Gardens and Natural History Museums in 11 European countries, to establish a collaborative learning network and expand their understanding of inquiry based science teaching (IBST). Suzanne Kapelari provides insight into the complex theoretical background and practical considerations that informed the project design and which guided the consortium through a three-year process of collaborative knowledge creation. 'Expansive Learning Theory' is fundamental to this approach and places emphasis on communities as learners, on transformation and creation of culture, on horizontal movement and hybridization of knowledge, and on the formation of theoretical concepts. This book is to be considered for planning and running international science education projects as well as a multifaceted theoretical underpinning of teaching. It serves as a conceptual and practical resource for formal and informal science educators and project managers. This project has received funding from the European Union's Seventh Framework Programme for research, technological development and demonstration under grant agreement no 266616."